Non-Visual Photopigments Effects of Constant Light-Emitting Diode Light Exposure on the Inner Retina of Wistar Rats - Benedetto, María M.; Guido, Mario E.; Contin, María A. (Frontiers in Neurology, 2017)
The retina is part of the central nervous system specially adapted to capture light photons and transmit this information to the brain through photosensitive retinal cells involved in visual and nonvisual activities. However, excessive light exposure may accelerate genetic retinal diseases or induce photoreceptor cell death, finally leading to retinal degeneration (RD). Light pollution (LP) caused by the characteristic use of artificial light in modern day life may accelerate degenerative diseases or promote RD and circadian desynchrony. We have developed a working model to study RD mechanisms in a low light environment using LED sources, at constant or long exposure times under LP conditions. The mechanism of photoreceptor cell death is still not fully understood. Our main goal is to study the biochemical mechanisms of RD. We have previously demonstrated that constant light (LL) exposure to white light emitting diodes (LED) produces a significant reduction in the outer nuclear layer (ONL) by classical photoreceptor cell death after 7 days of LL exposure. The photoreceptor cells showed TUNEL positive labeling and a caspase-3 independent mechanism of cell death. Here we investigate whether constant LED exposure affects the inner retinal organization and structure, cell survival and the expression of photopigments; in particular we look into whether constant LED exposure causes the death of retinal ganglion cells (RGCs), of intrinsically photosensitive RGCs (ipRGCs), or of other inner retinal cells. Wistar rats exposed to 200 lux of LED for 2 to 8 days (LL 2 and LL 8) were processed for histological, protein and DNA analysis. The results show no differences in the number of nucleus or TUNEL positive RGCs nor inner structural damage in any of LL groups studied, indicating that LL exposure affects ONL but does not produce RGC death. However, the photopigments melanopsin (OPN4) and neuropsin (OPN5) expressed in the inner retina were seen to modify their localization and expression during LL exposure. Our findings suggest that constant light during several days produces retinal remodeling and ONL cell death as well as significant changes in opsin expression in the inner nuclear layer (INL).